Polling the Public to Select Flagship Species for Tourism and Conservation—A ‘Big Five’ for the Peruvian Amazon? - Maribel Recharte; Phyllis C. Lee; Sarah‐Jane Vick; Mark Bowler (Ecology and Evolution)
ABSTRACT Flagship species are used to promote conservation and tourism. Africa's famous ‘Big five’ have become marketing flagships that fundraisers and tourism promoters emulate globally. Species can be selected systematically for marketing using characteristics such as colour, size or behaviour, but this approach can overlook unique animals or homogenise selections. Alternatively, polling the public can reveal existing preferences for animals directly. We used questionnaires with tourists in the Peruvian Amazon to identify existing biases for species and rank them for suitability for tourism and conservation marketing. Polling revealed several species that would not be considered good flagship candidates using systematic methods based on species characteristics. ‘Free listing’ tourists expressed preferences at inconsistent taxonomic levels. The response ‘monkeys’ (infraorder Simiiformes) was highest ranked, followed by ‘jaguar’ (Panthera onca), ‘Amazon dolphin’ (Inia geoffrensis), ‘sloths’ (suborder Folivora), and ‘caiman’ (subfamily Caimaninae) and ‘birds’ (class Aves). When ranking from a preselected shortlist, jaguar, Amazon dolphins and sloths (represented by Bradypus variegatus) remained popular, while vote splitting within higher taxonomic levels, in particular monkeys, made room for green‐winged macaw (Ara chloropterus) and anaconda (Eunectes murinus). When asked about their willingness to pay for excursions or donate to conservation, tourists were overwhelmingly more likely to quote larger figures for jaguars than any other species, but results for other species were more homogenous. Some popular taxonomic groups are diverse in Amazonia; up to 14 monkey species may be present at some sites Amazonia, alongside several hundred bird species. A Big five strategy obscures this diversity. Using physical characteristics as selection criteria underplays diversity and overlooks popular taxa—notably sloths for the Amazon. A strategy of polling the public to select popular species as flagships more directly identifies salient species for marketing and efficiently considers existing biases. However, diversity will trump a Big five approach in megadiverse areas.